Pendidikan Dan Kesetaraan Gender Di Sdi Cendekia Assalam Sebagai Upaya Pembentukan Karakter Siswa - Elsa Salsabila; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the implementation of gender equality and education as an effort to shape student character at SDI Cendekia ASSALAM. The study used a qualitative approach with a descriptive research type. The research subjects included the principal, teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that SDI Cendekia ASSALAM has implemented gender equality values ​​in the learning process, division of tasks, use of instructional language, and school activities inclusively without discriminating against gender. This implementation has a positive impact on student character formation, such as increased respect, empathy, self-confidence, mutual cooperation, and awareness of social justice. In addition, the school also strives to deconstruct gender stereotypes through fair learning and equal opportunities for all students. However, in its implementation, obstacles are still encountered in the form of cultural incompatibilities between the school and family environment and the absence of formal written guidelines regarding gender-responsive education. Therefore, the school implemented various strategic solutions, such as parenting programs and the development of SOPs for gender-responsive learning. This research shows that gender equality education has an important role in building students' character to be tolerant, inclusive, and respectful of differences from an early age